Thermal hysteresis of interface biased dipolar coupled nanoelements - Carriço, Artur da Silva (2013)
We report a theoretical investigation of thermal hysteresis of a pair of interface biased elliptical iron nanoelements, separated by an ultrathin layer of nonmagnetic material. The thermal hysteresis originates in the strong dipolar interaction, and is tunable by the nature of the low temperature state and the eccentricity of the nanoelements. The width of the thermal hysteresis varies from 500 K to 100 K for lateral dimensions of 125 nm × 65 nm and 145 nm × 65 nm.